Netflix: Branding strategies on Instagram - Abdala, Leonardo Ajavi Zaccaro; Carneiro, Mario Rubens de Oliveira (Seven Editora, 2024)
The continuous advancement of the Internet has significantly impacted how companies and their brands engage with their customers and key stakeholders. This has made it essential to focus on innovation in sales strategies and in brand presence, both areas which are constantly changing and adapting. The emergence of social media has, in turn, enabled new dynamics of interaction between people and companies, presenting a host of challenges and new possibilities. With internet-savvy consumers becoming increasingly critical and empowered, organizations aiming to manage their brands to generate positive results have been seeking to utilize these digital platforms to build healthier and more enduring relationships with their audience. In this context, this article presents a case study of Netflix – an American streaming video service company – which seeks to investigate aspects of the company's brand management on its Brazilian profile on the social media platform Instagram, a company owned by Meta (formerly Facebook). To achieve this, bibliographical research on the concepts of Branding, Brand Equity and digital marketing techniques was conducted, followed by analyses focused on both the text and image content of a sample of posts from the "Netflix Brazil" profile on Instagram, as well as their impact and receptivity among the streaming company's followers. These analyses not only helped to understand how the company communicates and positions itself in the digital environment, but also enabled the evaluation of the communication's effectiveness based on interactions with its followers. DOI:https://doi.org/10.56238/sevened2024.010-032